Microbiological profile of patients hospitalized in the intensive care unit of a public hospital in Baixada Maranhão (Research, Society and Development, 2022)
In the Intensive Care Unit (ICU) sector, whose objective is to stabilize the critically ill patient, invasive procedures are performed that break natural protection barriers, which associated with the epidemiological profile as well as the empirical initiation of antibiotics, favors the development of multidrug-resistant bacteria. , thus characterizing severe conditions with high morbidity and mortality. Thus, the present research aimed to determine the microbiological profile of cultures isolated from clinical specimens of patients admitted to the adult ICU of a public hospital in the Baixada Maranhense, through the collection of results obtained from examinations of microbial cultures. This is a cross-sectional, descriptive, retrospective study, with laboratory data from the year 2018. The data were tabulated and analyzed in Excel® spreadsheets, analyzed and described in absolute frequencies and percentages for the categorical variables and descriptive statistics of the numerical variable. From the results of 183 cultures, of bacteria and fungi, it was observed that 123 were from male patients and 60 from female patients. The mean age was 56.69 years (±21.89). The presence of microorganisms was detected in 139 blood cultures, 29 tracheal secretion cultures and 15 urine cultures. As for the antimicrobial profile, it was found that 30% of the microorganisms were sensitive to vancomycin, linezolid, gentamicin, teicoplamin, ciprofloxacin, meropenen and amikacin. Regarding the resistance profiles, there was greater resistance against penicillin and ciprofloxacin. These findings reinforce the need for stricter antimicrobial regimens aimed at greater control of the emergence of multidrug-resistant bacteria.